Stubble Burning- A Rationale for Asphyxiation of Macrocosm - S. Saumya Krishnan (Research Parks Publishing LLC, 2021)
Stubble burning is one of the major problems in India since last decade. During winter season mostly north India is blanketed under smog which is mostly contributed by farm stubble burning, causing pollution, low visibility, breathlessness to major three states & UT -Delhi, Punjab and Haryana. Its permanent solution is the need of the hour which involves the contribution of good governance, scientific aspects and cooperation. This article tries to highlight the various implications and way forward for this problem.